PENGARUH KUALITAS PELAYANAN, CASH ON DELIVERY, KETEPATAN WAKU PENGIRIMAN, DAN DISCOUNT FLASH SALE TERHADAP KEPUASAN PELANGGAN PENGGUNA SHOPEE. - Sismanto, Adi; Prayuda, Aris Firdian (Yayasan Insani Mandiri Santani, 2023)
From the results of the study, the effect on the variables of Service Quality and Cast On Delevery, Timeliness of Delivery and Discount Flash Sale on Customer Satisfaction of Shopee users in 5th semester students of the Management Study Program, Muhammadiyah University of Bengkulu. conclusions can be drawn as follows: Service Quality has a positive effect on Customer Satisfaction Shopee Users in 5th Semester Students of Management Study Program, University of Muhammadiyah Bengkulu. Cash On Delivery has a positive effect on Customer Satisfaction Shopee Users in 5th Semester Students of Management Study Program, University of Muhammadiyah Bengkulu. Timeliness of Delivery has a positive effect on Customer Satisfaction consumers on Shopee Customers in Semester 5 Students of Management Study Program, University of Muhammadiyah Bengkulu. Discount Flash Sale has a positive effect on Customer Satisfaction on Shopee Customers 5th Semester Students of Management Study Program, University of Muhammadiyah Bengkulu. Quality of Service , Cast On Delevery , Timeliness of Delivery and Discount Flash Sale has an effect on consumer satisfaction. This can be seen from the hypothesis test together (Simultaneously) Ftable > Fcount (12.749> 1.850). This is proven from the correlation analysis R = 0.713 (71.3%) and is almost close to 1. And the coefficient of determination is R2 = 0.509 or around 50.9% while 0.481 or 48.1% is a contribution of other variables not examined Keywords: Service Quality, Cash On Delivery, Timely Delivery, Discount Flash Sale, Customer Satisfaction.